Elevated osmolytes accumulation helps in combating NaCl stress causing negative impacts on growth and metabolism of Vigna radiata (L.) - Mir, Reyaz Ahmad; Logeshwari, T. R.; Aryendu; Somasundaram, R. (Journal of Plant Stress Physiology, 2024)
Salinity stress is one of the main abiotic stresses that have a negative impact on the growth performance of green gram. The current study was carried out as a result to find out growth, and morpho-biochemical changes in Vigna radiata CO7 variety cultivated under NaCl stress treatments. The V. radiata CO7 variety was selected and the experiment was carried out in pot culture under varying NaCl concentrations viz., 0, 50, 75, 100, and 125 mM respectively to assess maximum tolerance range of the CO7 variety. The salt stress was given on 15th days after sowing and sampling was done after 10 days of treatment on the 25th, 35th, and 45th day respectively. Salt stress results in a steep decline in shoot length, biomass, chlorophyll contents a and b, and soluble protein contents with increased NaCl treatments on all sampling days. However, carotenoid contents, and compatible solutes including proline, Glycine-betaine, Amino acids and total soluble sugars contents were found to be upregulated under varying NaCl concentrations in V. radiata CO7 variety on all sampling days. Thus, increased carotenoid contents, and osmolytes, provide stress tolerance to V. radiata CO7 variety by maintaining the turgor pressure of cells and preventing further water loss under varying NaCl concentrations. Hence, this variety shows maximum surveillance at 75 mM and beyond this plant performance is restricted and further study is needed to access CO7 variety for a breeding program to enhance salt stress tolerance.